Rapid diagnosis of neonatal sepsis in Pediatric population in tertiary care hospital, Durg - Chandrakar, Shiv Kumar; Bawankar, Smita; Panda, Animesh; Chandi, Dhruba Hari (Asian Journal of Medical Sciences, 2016)
Background: In under developing country Septicemia in infants to be of common occurrence with high morbidity & mortality. Aims and Objectives: Detection of rapid method for diagnosis of sepsis in paediatric age groups. Materials and Methods : Clinically suspected 369 cases of Bacteraemia in neonates, infants & children admitted as inpatients at CCM Medical College & Hospital, Durg & 45 healthy children as control were included in the present study. The cases were investigated by blood culture & 5 rapid tests Viz total leucocyte count (TLC), immature to total neutrophil ( I:T) ratio, C – reactive protein (CRP), ESR & Grams smears of Buffy coat for organisms. Results : Blood cultures were positive in 171 (46.34%) of 369 cases and negative organisms was 55.55% as against 44.44% of Gram positive bacteria. The most common isolates were Staph epidermides (24.56%) and Staph aureus (16.37%) with overall staphylococcal prevalence of 40.93% followed by gram negative bacteria, S.typhi (14.61%) E.coli 11.11% & Ps.auroginosa 10.52%. Conclusion : The rapid tests were evaluated in blood culture positive & negative cases CRP yielded maximum sensitivity of 70.76%, Specificity of 76.26% & positive predictive accuracy of 72.02%. Combination of 2 tests did not reveal any significant advantage over single CRP test. Asian Journal of Medical Sciences Vol. 7(3) 2016 94-96